Evaluation of the presence of drugs in sewage treatment station sludge before and after the bioremediation process by composting - Caminada, Suzete Maria Lenzi; Bocchiglieri, Miriam Moreira; Velini, Edivaldo Domingues [UNESP]; Paganini, Wanderley da Silva (FapUNIFESP (SciELO), 2023)
The presence of residual drugs in the environment is a growing global issue, with many studies seeking to quantify it. However, its behavior and effects, both on the environment and on humans are still mostly unknown. In this study, seven drugs were evaluated: Atenolol, Carbamazepine, Clonazepam, Ibuprofen, Paracetamol, Simvastatin, and Fluoxetine, from samples of sludge from a sewage treatment plant of the public system. The extraction of the compounds from the matrix was based on the leaching of the compounds in water and the analytical quantification was determined by an ultra-performance liquid chromatograph system, coupled to the mass spectrometer. The data indicate the possible movement of some drugs from aqueous to solid phase. We observed that the composting of the sludge could favor the biodegradation or mobilization of the compounds since there was a significant reduction in the concentrations, when comparing the values obtained before and after the composting process. The non-detection of a compound does not necessarily mean that it has been fully degraded by microorganisms; however, past studies reached similar results, which corroborates the adequacy of the methodological proposal and the adopted procedures, contributing to the production of reliable results.
Avaliação da presença de fármacos em lodo de estação de tratamento de esgotos, antes e após processo de biorremediação por compostagem
Keywords: Bioremediation; Composting; Pharmaceuticals; Sewage